Manhaj Sayyid Qutb dalam Berinteraksi dengan Ayat-Ayat Berkaitan Wanita di dalam Al-Quran: Sayyid Qutb's Methodology in Interacting with Quranic Verses Related to Women - Husain, Husna; Hashim, Ibrahim (Perspektif Jurnal Sains Sosial dan Kemanusiaan, 2017)
In the Quran there are few verses state about women and matters related to them. Based on research methodology of inductive , all contents of Tafsir Fi Zilal Al-Quran were analysed. This paper identifies the characteristics of verses related to women besides analyses the methodologies used by SayyidQutb in interacting with these verses with relevant examples. Finally, this paper identifies his attitude and stand over the position of women and matters related to them.